Revitalisasi Bahasa Bali Generasi Muda Melalui Studi Kualitatif Pada Era Digital di Denpasar - Noviana Dewi, Komang Candra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This study explores the revitalization of the Balinese language in the digital era, focusing on the younger generation in Denpasar. As globalization, shifting social norms, and the dominance of Indonesian and foreign languages accelerate, Balinese faces a critical decline in daily use, especially in digital spaces. Using a qualitative method, data were gathered through observations in schools, communities, and social media, as well as document analysis, literature review, and online data exploration. The research reveals that although initiatives like language competitions, local content curricula, and digital educational materials have been introduced, actual usage among youth remains minimal and mostly symbolic. The findings highlight that revitalization efforts must go beyond formal activities and adapt to the digital habits of today’s youth. Innovative, collaborative strategies involving government institutions, educational bodies, cultural communities, and digital platforms are crucial to make Balinese language vibrant and relevant. Sustainable preservation requires embedding the language naturally into the everyday digital experiences of young people, ensuring its survival and growth in the modern era.